Existence and stability analysis of solutions for a new kind of boundary value problems of nonlinear fractional differential equations - Liu, Weiwei; Liu, Lishan (Nonlinear Analysis: Modelling and Control, 2022)
This research work is dedicated to an investigation for a new kind of boundary value problem of nonlinear fractional differential equation supplemented with general boundary condition. A full analysis of existence and uniqueness of positive solutions is respectively proved by Leray–Schauder nonlinear alternative theorem and Boyd–Wong’s contraction principles. Furthermore, we prove the Hyers–Ulam (HU) stability and Hyers–Ulam–Rassias (HUR) stability of solutions. An example illustrating the validity of the existence result is also discussed.